2020
DOI: 10.1155/2020/7286958
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium Tanshinone IIA Sulfonate Attenuates Erectile Dysfunction in Rats with Hyperlipidemia

Abstract: Hyperlipidemia is considered one of the most important risk factors for erectile dysfunction (ED). To determine the effect of sodium tanshinone IIA sulfonate (STS) as an antioxidant agent on ED in high-fat diet- (HFD-) induced hyperlipidemia in rats and to investigate if STS administration could improve erectile function via hydrogen sulfide (H2S) production by inhibition of oxidative stress. Hyperlipidemia was induced in Sprague-Dawley rats by feeding HFD for 16 weeks. The rats were randomly divided into 3 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A complex mechanism by which H 2 S relaxes smooth muscles in the penis may involve activating BKCa and Kv channels, inhibiting RhoA/ROCK signaling pathways, and raising cGMP levels to bypass NO pathway. Recently, selective b3 agonists such as mirabegron (75) and natural extracts such as RVT (79) and STS (77) have been shown to improve ED, with both classes of compounds being at least partly dependent on H 2 S. Besides, the relaxation of bladder smooth muscle by H 2 S has been shown to improve LUTS and subsequent ED. Consequently, the multifaceted therapeutic benefits of H 2 S offer potential for reducing medication dosages and enhancing the quality of life for patients with both conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complex mechanism by which H 2 S relaxes smooth muscles in the penis may involve activating BKCa and Kv channels, inhibiting RhoA/ROCK signaling pathways, and raising cGMP levels to bypass NO pathway. Recently, selective b3 agonists such as mirabegron (75) and natural extracts such as RVT (79) and STS (77) have been shown to improve ED, with both classes of compounds being at least partly dependent on H 2 S. Besides, the relaxation of bladder smooth muscle by H 2 S has been shown to improve LUTS and subsequent ED. Consequently, the multifaceted therapeutic benefits of H 2 S offer potential for reducing medication dosages and enhancing the quality of life for patients with both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…ED has been associated with defects in the L-Cys/H 2 S pathway (76). The levels of H 2 S synthases are decreased to varying degrees in the penile tissues of rats with ED caused by radical prostatectomy, hyperlipidemia, diabetes, or hypertension (27,42,44,77). This phenomenon suggests that ED can be treated with exogenous H 2 S supplementation.…”
Section: Therapeutic Targets and Future Perspectives To Treat Edmentioning
confidence: 99%
“…An injury to one or more parts of the penis can result in erectile dysfunction (ED). It has been determined that rats with ED due to radical prostatectomy, hyperlipidemia, diabetes, or hypertension have reduced levels of H 2 S-generating enzyme in their penile tissues [19,51,68,69]. Furthermore, La Fuente et al reported that ED is associated with defects in the L-cysteine/H 2 S pathway [70].…”
Section: H2s Relieves Erectile Dysfunctionmentioning
confidence: 99%
“…It appears that RVT-stimulated CC relaxation is partly dependent on H 2 S production and is not dependent on NO production. Furthermore, it was discovered that sodium tanshinone IIA sulfonate (STS) [69] reversed the downregulation of CBS and CSE and inhibited H 2 S production in rats fed a high-fat diet (HFD). Additionally, STS guarded against ED through the activation of the Nrf2/HO-1 pathway in response to HFD-induced oxidative stress.…”
Section: H2s Relieves Erectile Dysfunctionmentioning
confidence: 99%
“…In the article titled “Sodium Tanshinone IIA Sulfonate Attenuates Erectile Dysfunction in Rats with Hyperlipidemia” [ 1 ], there was a spelling error in author Qinyu Zeng's name in the author list, where “Qingyu Zeng” should have read “Qinyu Zeng.” This is corrected as shown above.…”
mentioning
confidence: 99%